2014
DOI: 10.1016/j.sjpain.2014.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pain and Quality of Life—Findings from the Swedish National Study on Aging and Care—Blekinge study

Abstract: Background and aims The influence of pain as well as Quality of Life (QoL) varies in accordance with biological, social, psychological and existential factors. This study investigates the influence of such factors on the relationship between pain and QoL among older adults from a gender perspective. Methods The Swedish National Study on Aging and Care (SNAC-Blekinge) baseline sample comprised 1402 individuals aged 60-96 years, of whom 769 (55%) reported pain. The participants were invited by a letter to take p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
1
6
0
2
Order By: Relevance
“…Embora o foco do presente estudo tenha incidido na relação entre a violência e os componentes físico e mental da QVRS de idosos, cabe ressaltar que outras variáveis também se mostraram significativamente associadas aos desfechos analisados. As associações com incapacidade funcional para atividades da vida diária, multimorbidade, dor e sintomas depressivos são congruentes com outros estudos 16,[53][54][55][56] e ratificam a necessidade de detecção e manejo de condições físicas e psíquicas que possam comprometer a QVRS de idosos.…”
Section: Discussionunclassified
“…Embora o foco do presente estudo tenha incidido na relação entre a violência e os componentes físico e mental da QVRS de idosos, cabe ressaltar que outras variáveis também se mostraram significativamente associadas aos desfechos analisados. As associações com incapacidade funcional para atividades da vida diária, multimorbidade, dor e sintomas depressivos são congruentes com outros estudos 16,[53][54][55][56] e ratificam a necessidade de detecção e manejo de condições físicas e psíquicas que possam comprometer a QVRS de idosos.…”
Section: Discussionunclassified
“…Lena Sandin Wranker and co-workers [1] confirm that a low health related quality of life is associated with chronic pain, especially in women. This has been documented repeatedly by others, e.g.…”
Section: Low Health Related Quality Of Life With Chronic Pain Increamentioning
confidence: 93%
“…The older male persons in the Lena Sandin Wranker et al [1] survey were suffering more from insomnia than the female persons, and their insomnia was associated with low QoL.…”
Section: Older Men's Health Problems Cause Insomnia and Low Quality Omentioning
confidence: 95%
“…Gender must also be taken into consideration in studies on older caregivers, as pain is reported more frequently among elderly female caregivers than their male counterparts [21]. Kristensson Ekwall et al [22] found that female caregivers were more vulnerable to the negative consequences of caregiving, as they found less satisfaction in care than males did and therefore might require greater consideration as family caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…This should preferably be supplemented with other, more detailed measures of quality of life when used among older people, as it is short (fewer questions make it easier to answer) and does not include questions about work [24]. In literature, it has been stressed that the relations between mobility, functional ability, and HRQoL are important to consider in older people with pain [21], since pain may affect mobility and functional ability, as well as HRQoL.…”
Section: Introductionmentioning
confidence: 99%